Correction: Correlates of HIV treatment adherence self-efficacy among adolescents and young adults living with HIV in southwestern Uganda. - Scholastic Ashaba; Charles Baguma; Patricia Tushemereirwe; Denis Nansera; Samuel Maling; Brian C Zanon; Alexander C Tsai (PLOS Global Public Health, 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0003600.].